Policy of Development for Juvenile Delinquency in the Perspective of Indonesian Criminal Justice System Reform (Study on Institute for Special Development Children LPKA Kutoarjo, Central Java, Indonesia) - Wangi, Yosefin Dika Tyas (Faculty of Law, Universitas Negeri Semarang, 2017)
One of the functions of Penitentiary Institution becomes an institution that basically conducts guidance to socialize the convicts back after the court decision. But in the perspective of society that prisons are a place to punish people and form a negative image in society. The succession of the Children's Penitentiary to become LPKA (Lembaga Pembinaan Khusus Anak) based on Law No.11 of 2012 seeks to change the perception of child counseling in the institution that fostered Delinquency children. But erasing the image in the community is not easy in the short term to understand the community about the function of LPKA. Thus raises the issue of Juvenile Delinquency development policy after the court decision that can be done by LPKA. Therefore, it is necessary to have policies that can be felt by the assisted citizens with special forms of protection for the children one of them is by way of mental, spiritual, and social guidance for the children in the Institute for Special Development of Children (LPKA). This paper discusses two important points, namely: first how is the policy of LPKA Kutoarjo in conducting development of juvenile delinquency, and second, what is the policy that should be towards the development of juvenile delinquency in the future.